Association of Dengue Disease with ABO RH Blood Group - Badi Uddin, Pordil Khan, Ammar Bin Saad, Sajid Ali, Ayesha Muneer, Mehwish Bibi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dengue viral infection is a global public health issue. Several viral and other host factors are the contributed factors including the ABO blood group for transmission of dengue virus (DENV). ABO blood groups have been shown to involve in the intensity of DENV. This study aims to find the association ABO and Rh blood group with DENV infection. Methods: This cross-sectional study was conducted in tertiary care hospital. All DENV NS-1 positive patients were included irrespective of age and gender. The blood group of all DENV-infected patients was determined through ABO and Rh anti-sera (forward blooding grouping). Descriptive data were analyzed through SPSS and Microsoft Excel. Results: Among a total of 105 dengue-infected patients, male were 68 patients and female were 37 patients. The highest number of cases were found in the age group 21-30 years and 11-20 years. The predominant blood group was found A positive in dengue viral infected patients while AB negative blood group was found common in Rh negative blood groups. Conclusion: Blood group A positive and AB negative patients in Rh positive and Rh negative blood groups had more risk of dengue viral infection as compared to other blood groups. Further studies are necessary to find the severity of patients with different blood groups. Based on their differential distribution in the community and their correlation with mosquito performance, it can be deduced that the risk of contracting dengue infection differs with the ABO and Rh blood groups. Additional study is necessary to determine whether HLA, dengue serotype, and ABO are experimental/predictor factors, and whether certain blood subgroups are associated with a disproportionately higher risk of dengue virus infection. Keywords: Dengue viral infection, Serotype, Anti-A, Anti-B, Anti-D, ABO, Rh blood group